2021
DOI: 10.1039/d0nj04800c
|View full text |Cite
|
Sign up to set email alerts
|

Cu(ii)-Porphyrin based near-infrared molecules: synthesis, characterization and photovoltaic application

Abstract: Three novel Cu(ii)-porphyrin-based near-infrared non-fullerene acceptors were developed, which show strong intramolecular charge transfer absorption spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The mass spectrum indicated the structure of as‐prepared sample as CuTAPP (m/z = 736.2, Figure S1, Supporting Information). [ 23 ] Both scanning electron microscopy (SEM, Figure S2, Supporting Information) and transmission electron microscopy (TEM, Figure S3a, Supporting Information) images showed that CuTAPP was amorphous, with uniform distributions of Cu, N, and C elements across the whole sample.…”
Section: Resultsmentioning
confidence: 99%
“…The mass spectrum indicated the structure of as‐prepared sample as CuTAPP (m/z = 736.2, Figure S1, Supporting Information). [ 23 ] Both scanning electron microscopy (SEM, Figure S2, Supporting Information) and transmission electron microscopy (TEM, Figure S3a, Supporting Information) images showed that CuTAPP was amorphous, with uniform distributions of Cu, N, and C elements across the whole sample.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the use of other central metals such as Cu(II) in the porphyrin core has been scarcely used in OSCs, and the studied devices presented low efficiencies (≤3%). [44,45] These outcomes demonstrated that metalloporphyrins, which are different from Zn-porphyrins, also have great potential for the design of NFSMAs for efficient OSCs.…”
Section: Introductionmentioning
confidence: 99%